2021
DOI: 10.4236/jbm.2021.910011
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Intravascular Coagulation at Diagnosis in Acute Myeloblastic Leukaemia

Abstract: Background: Disseminated Intravascular Coagulation (DIC) is a life threatening complication frequently observed in acute leukemia. Among the morphological varieties of Acute Myeloid Leukaemia (AML), Acute Promyelocytic Leukaemia (APL) is well established to cause DIC. But there have been reports noted that abnormal DIC parameters also commonly observed in the patients with non-APL AML. This study evaluated the DIC parameters & DIC score according to International Society of Thrombosis and Haemostasis (ISTH) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Accordingly, we can conclude that many of our cases had advanced DIC. Chowdhury et al [20] found that only PT and D-Di were significantly higher in overt DIC. On the other hand, Aggarwal et al [25] reported that only platelets and D-Di levels were significantly different between the overt DIC and non-DIC patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Accordingly, we can conclude that many of our cases had advanced DIC. Chowdhury et al [20] found that only PT and D-Di were significantly higher in overt DIC. On the other hand, Aggarwal et al [25] reported that only platelets and D-Di levels were significantly different between the overt DIC and non-DIC patients.…”
Section: Discussionmentioning
confidence: 96%
“…In two separate studies from Serbia, DIC was found in 42% of AML; in the other one done over APL patients, it was observed in 84% [16,17]. Other studies reported variable rates of overt-DIC in non-APL AMLs ranging from 6.4% to 25.2% [18][19][20]. These diverse rates are attributed mostly to the differences in the enrolment criteria and different scoring systems used for diagnosing overt DIC by different studies [5].…”
Section: Discussionmentioning
confidence: 99%
“…The similarities and disparities in these results may be explained by the differences in the characteristics of the studied cohorts including leukemic subtype, age, and gender. 18,19 Nearly one third of the current AL patients had reduced levels of natural coagulation inhibitors; PC in 34.5%, PS in 28.6%, and AT in 26.2% of the patients. The reduction in PC and PS could be attributed to the cytokine release in AL and the systemic inflammation which leads to the down regulation of thrombomodulin and consequently lowering the PC and PS.…”
Section: Httpsmentioning
confidence: 99%